1997
DOI: 10.1063/1.473870
|View full text |Cite
|
Sign up to set email alerts
|

Photoionization studies of manganese clusters: Ionization potentials for Mn7 to Mn64

Abstract: The photoionization spectra of manganese clusters consisting of between seven and sixty-four atoms have been measured near threshold. As for other transition metal clusters previously investigated, the ionization potentials (IPs) decrease rapidly but nonmonotonically up to n≅20 and more slowly and smoothly beyond that. No correlation is observed between Mnn IPs and their reactivity toward molecular hydrogen, reported previously by Parks et al. [J. Chem. Phys. 104, 3531 (1996)]. In particular, the absence of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 38 publications
5
23
1
Order By: Relevance
“…For Mn 8 the experimental ionization energy is observed to be 4.91 eV. 27 We performed an SCF calculation on the positively charged Mn 8 cluster and find it to lie 5.49 eV above the neutral Mn 8 cluster. In contrast to the ionized Mn 7 cluster, the ionized Mn 8 cluster has an open minority spin shell with two electrons occupying three degenerate states.…”
Section: B the Larger Ferromagnetic Clusters: Mn 4 -Mnmentioning
confidence: 91%
“…For Mn 8 the experimental ionization energy is observed to be 4.91 eV. 27 We performed an SCF calculation on the positively charged Mn 8 cluster and find it to lie 5.49 eV above the neutral Mn 8 cluster. In contrast to the ionized Mn 7 cluster, the ionized Mn 8 cluster has an open minority spin shell with two electrons occupying three degenerate states.…”
Section: B the Larger Ferromagnetic Clusters: Mn 4 -Mnmentioning
confidence: 91%
“…Manganese clusters were produced via pulsed laser vaporization of a cylindrical manganese target (99.99%, Ames Materials Preparation Center, Ames, Iowa 16 ) through which helium was flowed continuously. The laser vaporization source was coupled to a high aspect ratio flow tube ͑9 cm lengthϫ 0.3 cm diameter͒ held at 68± 2 K. 17 The residence time of the clusters within the flow tube ͑ϳ4 ms͒ was sufficient to ensure that they were equilibrated to the flow tube temperature prior to expansion into vacuum. 18 At the helium flow rates used ͑ϳ1000 sccm͒, the pressure within the flow tube was 10± 1 Torr.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Our previous photoionization studies 17 have suggested that Mn 13 may be produced in (at least) two isomeric forms, in which case the experimentally measured moment ͑ = 0.54± 0.06 b ͒ is an average value weighted according to the relative abundances of the isomers in the beamquantities that cannot be determined with high precision. Nayak, Nooijen, and Jena 51 found three isomers for Mn 13 : icosahedral (ground state, = 2.54 b per atom), hexagonallike (⌬E = + 0.05 eV, 1.31 b per atom), and cuboctahedral (⌬E = + 0.44 E, 0.39 b per atom).…”
Section: Mn 13mentioning
confidence: 99%
“…On the experimental side, photoelectron spectra were obtained for Mn n − , n = 3-8, 24 and Mn 13 − , 25 whereas energies of electron detachment from neutral Mn n clusters have been measured 26 in the range 7 ≤ n ≤ 64. Stern-Gerlach experiments were performed for Mn n clusters in two ranges: 11 ≤ n ≤ 99 27 and 5 ≤ n ≤ 22.…”
Section: Introductionmentioning
confidence: 99%